The Influence of Profitability, Asset Structure, Company Size, Corporate Governance, and Investment Opportunities on Stock Prices with Stock Returns as a Moderating Variable - Pamungkas, Putri; Achyani, Fatchan; Witono, Banu (Journal of Accounting and Finance Management, 2024)
The capital market is a market that acts as a mediator between investors, companies and government institutions in offering various long-term financial securities. With the aim of generating income, investors utilize the capital market as a means for growth and expansion of the Company's business, reflecting the Company's willingness to be open in expanding and maintaining its business. This research examines the influence of Profitability, Asset Structure, Company Size, Corporate Governance, and Investment Opportunities on Stock Prices with Stock Returns as a Moderating Variable. The sample used in this research was 28 manufacturing companies listed on the Indonesia Stock Exchange (BEI) indexed LQ45 in the 2020-2022 period. The sample was determined using the purposive sampling method. This research uses multiple linear regression analysis and is processed using SPSS25. The results of the research show that: (1) Profitability has a positive and significant effect on Share Prices (2) Asset Structure has no significant effect on Share Prices (3) Company Size has a positive and significant effect on Share Prices (4) Corporate Governance has no significant effect on Share Prices (5) Investment Decisions have a positive and significant effect on Stock Prices (6) Stock Returns strengthen or moderate Profitability have a positive and significant effect on Stock Prices (7) Stock Returns do not strengthen or moderate Asset Structure on Stock Prices (8) Stock Returns do not strengthen or does not moderate Company Size on Share Prices (9) Stock Returns do not strengthen or moderate Corporate Governance on Share Prices (10) Stock Returns strengthen or moderate Investment